The Cognition Checklist for Mania—Revised (CCL-M-R): Factor-Analytic Structure and Links with Risk for Mania, Diagnoses of Mania, and Current Symptoms - Fulford, Daniel (2009)
We conducted two studies to examine the Cognition Checklist for Mania—Revised (CCL-M-R; Beck, Colis, Steer, Madrak, & Goldberg, 2006). In the first, we gathered data in an undergraduate sample (N = 208) to examine the factor structure of the measure and the correlations of the subscales with the Hypomanic Personality Scale (HPS; Eckblad & Chapman, 1986). Factor analyses refined subscales, and three of the original four subscales developed by Beck and colleagues (2006) were retained. Persons with higher stores on the HPS were likely to endorse manic cognitions associated with overconfidence and excitement-seeking. In a second study, we gathered data from 61 persons diagnosed with bipolar I disorder, 38 with major depressive disorder (MDD), and 33 with no history of mood disorder. Excitement-seeking scores were robustly related to current manic symptoms, as measured by the Internal State Scale (ISS; Bauer et al., 1991). Thus, CCL-M-R excitement-seeking scores appear to be related to risk for mania and to current symptoms of mania within a clinical sample. Other findings, though, suggest that problems with interpersonal relationships (feeling thwarted by others) may emerge among those clinically diagnosed with bipolar I disorder, even though not endorsed among those at risk. Moreover, difficulties with interpersonal relationships and diminished confidence in those with bipolar I disorder paralleled the difficulties observed among those with MDD. Findings suggest that cognitive profiles associated with mania may depend on mood state and course of the disorder.